Occult Autoimmune Background for Epilepsy—The Preliminary Study on Antibodies Against Neuronal Surface Antigens - Dziadkowiak, Edyta; Moreira, Helena; Buska-Mach, Katarzyna; Szmyrka, Magdalena; Budrewicz, Sławomir; Barg, Ewa; Janik, Marta; Pokryszko-Dragan, Anna (Frontiers in Neurology, 2021)
Objective: To determine incidence of antibodies against neuronal surface antigens (NSA-ab) in the patients with different types of epilepsy, in comparison with the subjects diagnosed with immune-mediated disorders. Methods: 56 patients with drug – resistant idiopathic or post-stroke epilepsy and 23 ones with immune-mediated disorders were involved. NSA-ab were sought in serum using indirect immunofluorescence method (IIFT Autoimmune Encephalitis Mosaic 6 test). Relationships were analyzed between presence of NSA-ab and clinical presentation. Results: NSA-ab were detected in the sera from seven patients: anti-DPPX in 1 patient, anti-AMPAR1/R2 in 2, anti-LGI1 in 1; in one case both anti-CASPR2 and DPPX IgG. Out of these 5 patients, 3 represented subgroup the immune-mediated disorders and 2 - drug-resistant epilepsy. None of the patients with post-stroke epilepsy was positive for NSA-ab. Significance: Autoimmune etiology should be considered in patients with drug-resistant epilepsy of unknown origin. NSA-ab seem not to be related to epilepsy resulting from ischemic brain injury. Presence of NSA-ab in patients with immune-mediated inflammatory disorders, especially without clinical signs of CNS involvement, may be caused by unspecifically enhanced autoimmune reactivity.